solve 7 5/10 − 1 6/10 . What is the correct result?

1 answer

To solve the expression 7 5/10 - 1 6/10, we first need to convert both mixed numbers to improper fractions.

7 5/10 can be written as 7 + 5/10. To convert 5/10 to an improper fraction, we divide the numerator (5) by the denominator (10):

5 ÷ 10 = 1/2.

Therefore, 7 5/10 can be written as 7 + 1/2 = 7 1/2.

Similarly, 1 6/10 can be written as 1 + 6/10. Converting 6/10 to an improper fraction:

6 ÷ 10 = 3/5.

So, 1 6/10 is equal to 1 + 3/5 = 1 3/5.

Now that both mixed numbers have been converted to improper fractions, we can subtract:

7 1/2 - 1 3/5

To subtract fractions, we need to find a common denominator. In this case, the least common denominator (LCD) is 10:

1/2 = 5/10
3/5 = 6/10

Now subtract the fractions:

7 5/10 - 1 6/10 = (7 - 1) + (5/10 - 6/10)
= 6 + (-1/10)
= 6 - 1/10

Combining the whole number and fraction:

6 - 1/10 = 6 9/10

Therefore, the correct result is 6 9/10.
Similar Questions
    1. answers icon 0 answers
    1. answers icon 1 answer
    1. answers icon 1 answer
  1. Put in the correct orderSolve exponentiation. Solve multiplication and division. Solve operations within parentheses Solve
    1. answers icon 1 answer
more similar questions